The Travels of Robert Lyall, 1789–1831 - Campbell, Gwyn. author. aut Link
XIX, 415 p. 49 illus., 33 illus. in color.
Keywords: This book explores the life of Robert Lyall, surgeon, botanist, voyager, British Agent to the court of Madagascar. Born the year of the French Revolution, Lyall grew up in politically radical Paisley, Scotland, before studying medicine, in Edinburgh, Manchester, and subsequently St. Petersburg, Russia. His criticism of the Tsar and Russian aristocracy led to an abrupt departure for London where Lyall became the voice of liberalism and calls for political reform, before appointed British Resident Agent in Madagascar in 1827, representing the interests of the Tory establishment that he had hitherto so roundly castigated. However, Lyall discovered that the Malagasy crown had turned against the British alliance of 1820, his scientific pursuits alienated the local elite, and his efforts to re-establish British influence antagonized the queen, Ranavalona I, who accused Lyall of sorcery and forced him and his burgeoning family to leave for Mauritius where he died an untimely death, of malaria, in 1831.